Posterior Estimators of Characteristics of Acceptance Inspection of Kinescopes Glass Parts - Kalnius, R.; Vaišvila, A.; Eidukas, D. (Elektronika ir Elektrotechnika, 2004)
Posterior estimators of kinescope acceptance inspection characteristics for continual and accidental inspection cases are established.For spot check inspection with unaccepted lots with continual re-inspection the spot estimators’ values for interval estimators’calculation are given. For such acceptance inspection estimators’ models are made for two initial data forming variants, using betadistribution for probability defectiveness level description. Received models are compared with known unbiased estimators’ models, andtheir advantage with respect to estimators’ stability is ascertained. It is shown that the provided variants allow assessing of initial datacorrectness. Ill. 4, bibl. 10 (in Lithuanian; summaries in Lithuanian, English and Russian).